Comparative Study of IGFBP Properties in Toad and Rat Sera - Cortizo, Ana María (1993)
The levels ofIGF-Ihave been simultaneously measured byradioimmunoassayin samples of the toadBufo arenarumand of normal male Wistar rats. In addition, the different fractions of IGF-I binding proteins (IGFBP) and their binding properties have been identified by ligand blot and Scatchard analysis in the serum of both species. In the toad, we have measured levels of IGF-I (2.78 ± 0.48 ng/ml) similar to those previously reported in amphibians but far below those found in rats. IGFBP levels were estimated at 129 ± 23 and 4249 ± 321 pg/ml in toad and rat serum samples. Two main IGFBP fractions of 30-34 kDa, accompanied by a minor component of 24 kDa and seldom by another of 40 kDa, were identified in toad serum. In rat serum—as already reported—three bands of 40, 30, and 24 kDa were identified, the first being the main component and the last the minor one. The Scatchard analysis of a competitive binding assay showed two types of binding sites in toad serum: one of high affinity-low capacity (Ka1= 1.6 × 1010M-1;R1= 1.2 × 10-11M) and another with low affinity-high capacity (Ka2= 1.9 × 108M-1;R2= 1.9 × 10-10M). The percentage fraction of these binding sites occupied by IGF-I was 13.5%. The figures for K1and K2were lower and those for R1and R2were higher in rat than in toad serum. The percentage fraction of occupied ratIGFbinding sites was 3.6%. The IGF carrier levels (IGFBP5) estimated in our laboratory in samples of rat and toad serum gave figures that were almost 33 times lower in the latter than in the former. Hence, the fraction of free and bound IGF-I in toad and rat blood might be different. Our results provide new evidence of the presence and the properties of IGFBP in amphibians, confirming the wide distribution of this carrier among different species and its possible role as modulator of IGF-I biological effects.